O Acervo da divisão de ordem política e social do Estado do Pará: recolhimento, tratamento e acesso - SILVA, Jonas Mescouto da (2023)
This course completion work (TCC) aims to describe the activities of identification and collection, treatment and access to the DOPS/PA archives, belonging to the archival collection of the Secretariat of Public Safety (SEGUP), held by the Public Archive of the State of Pará (APEP). The specific objectives were to present the SEGUP and DOPS/PA; to contextualize the APEP and the identification and collection activities of the DOPS/PA collection; and to present the collection based on its documental treatment and access. To carry out this work, the method of qualitative documentary research and bibliographical survey was used, as well as an APEP report on the DOPS/PA collection and a semi-structured interview with the director of APEP. As a result, it was possible to understand, through historical contextualization, the production of these documents, and the origin and storage of them, as well as their role in society. Thus, it is possible to conclude that the availability of these documents can contribute to future research and the promotion of rights, helping to better understand the historical period in which these documents were created and operational ways of DOPS/PA.